Violations Of Grice’s Maxim - Ni Kadek Mirayanti; Ni Luh Sutjiati Beratha; Ni Wayan Sukarini (FKIP, Universitas Palangka Raya, 2024)
Violations in conversation are found not only in everyday life when people interact with other people, but also, in drama and films performed by characters, in novels, interviews, debates, and other forms of social interaction performed for various reasons. This study examines the violations of Grice's Maxim in the movie Jack Reacher: Never Go Back, focusing on the characters' conversational utterances. Using observation method and note-taking technique, the descriptive qualitative method was applied, analyzing data using the Theory of Cooperative Principles and Context of Situation. The results showed twenty-nine data of conversation were violated by the characters in the movie. Maxim of Quality (51,7%), Maxim of Quantity (13,8%), Maxim of Relation (10,4%), and Maxim of Manner (24,1%).